2013
DOI: 10.1111/1471-0307.12090
|View full text |Cite
|
Sign up to set email alerts
|

Species distribution, molecular characteristics and vancomycin resistance gene profiles of Enterococcus sp. isolates from farmhouse cheeses in western Turkey

Abstract: Species distribution, virulence traits and vancomycin resistance gene profiles of Enterococcus isolated from 43 home-made artisan cheese samples collected from open markets, located in Aydin region of Turkey, were investigated. Of the 129 isolates, 95 were identified as Enterococcus sp.; Enterococcus faecium being the most prevalent species (82.1%), followed by Enterococcus faecalis (13.6%) and Enterococcus durans (1.0%). None of the enterococci were harbouring vanA or vanC, while seven isolates (7.3%) were sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 46 publications
(118 reference statements)
1
3
0
Order By: Relevance
“…In accordance with ÖZMeN tOĞAY et al (2010) and BuyukyOruk et al (2014), the gelE virulence gene was most commonly detected in isolates, and some isolates carried more than one virulence gene at the same time. SaNteSVaN et al (2015) detected ace, gelE, asa and cylA genes with percentages of 68%, 54%, 22% and 4% in enterococci recovered from fecal samples of wild fur seals.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In accordance with ÖZMeN tOĞAY et al (2010) and BuyukyOruk et al (2014), the gelE virulence gene was most commonly detected in isolates, and some isolates carried more than one virulence gene at the same time. SaNteSVaN et al (2015) detected ace, gelE, asa and cylA genes with percentages of 68%, 54%, 22% and 4% in enterococci recovered from fecal samples of wild fur seals.…”
Section: Discussionsupporting
confidence: 86%
“…In this study, ent1 and ent2 primers (ella Biotech Gmbh, Martinsried, Germany) described by ke et al (1999) were used ( VaNkerCkhOVeN et al (2004), COque et al (1995), WILLeMS et al (2001) were used for this purpose (table 1). PCr reaction mixture and amplification conditions were carried out according to VaNkerCkhOVeN et al (2004) and BuyukyOruk et al (2014), as previously reported. Determination of antimicrobial susceptibility.…”
Section: Confirmation Of Enterococci At Genus Level By Pcr Assaymentioning
confidence: 99%
“…Whilst the Saudi research (Buyukyoruk et al, 2014) whose study included two types of enterococci the percentage of appearance of the VanB gene was 7.3% while the percentage of the appearance of this gene in this study was 6.66%. The two researchers (Mirani and Jamil, 2013) they selected two isolates of Staphylococcus aureus the first from pus and the second from the blood of a patient after a heart operation, his results showed that the bacterial isolate from the blood was harboring the VanA cluster which is present on the plasmid DNA as for the second isolated from pus it was intermediate resistant and the results of the genetic examination by PCR technique showed that it did not contain the genes VanA, VanB and VanC, Thus through its results the percentage of appearance of the VanA gene in their study became 50% which is very close to the percentage of appearance of the same gene in this study (40%).As for the researcher (Dahl et al, 2007) where their study was about Enterococcus ssp bacteria and the presence of VanA, VanB and VanC genes on chromosomal and plasmid DNA, fourteen strains were selected 9 of them clinically human and five isolates from poultry all of which are faecal samples and the most important results were the presence of two isolates in which no gene appeared and three isolates in which the VanB gene was found on the chromosomal DNA with a percentage of 21.42% and only one isolate was found in which the VanB gene was found on the chromosomal and plasmid DNA with a percentage of 7.14% and this percentage is very close to the percentage that was obtained in our study (6.66%).…”
Section: Discussionmentioning
confidence: 65%
“…Gelatinase, encoded by gelE gene, hydrolyses diverse biological peptides such as gelatin, collagen and casein. Another virulence trait cytolysin (cyl) is an extracellular toxin, which lyses array of procaryotic and eucaryotic cells (Buyukyoruk et al, 2014). Due to its antimicrobial resistance and virulence factors, enterococci has been not considered generally recognised as safe (GRAS) bacteria and has been known as emerging pathogen of humans.…”
Section: Introductionmentioning
confidence: 99%